(untitled) (Tzintzun, Revista de Estudios Históricos, 2016)
In this Bicentennial year, to reflect on the process of building the Mexican state is doing on the components of their national identity. In this context, the religious question is, presented as a relevant explanatory factor. In its base, state nationalism found in the ecclesiastical institution a major obstacle. Especially because it had established itself as a community trans-historical, essential, beyond and outside of politics. A pole of strength capable of generating membership and provide identity to the social bases. From 1821 to 1917, the transfer of legitimacy from political to religious institutions ‘was a complex evolution. The revolutio-nary balance involved the establishment of a secular model and hence the separation of the religious beliefs of the public sphere. After the 1992 reform, the adoption of secularism as an essential element of democratic pluralism has led to some reinterpretation of the system, according to the requirements of intemational law. For the Mexican Episcopate, 2010 has served as an occasion to offer an alternative view of official history. A church-state interaction edges which largely explains the processes of political change in contemporary Mexico.